Diseccionando el diseño centrado en las personas: Anatomía de un proyecto real en contexto guatemalteco - Bonilla Barillas, Melissa (2025)
Lecture at University Rafael Landivar (URL) Guatemala City Octuber 1st 2025 Title: "Dissecting Human-Centered Design" Anatomy of a real project in a Guatemalan context. Participants: 10 (Researcher from IARNA and ICESH) A space to share and discuss the implementation of the Human-Centered Design (DCH) approach in Guatemala. A presentation to describe the methods applied for the creation, validation and implementation of agroclimatic bulletins in the departments of Chimaltenango, Santa Rosa and Zacapa. And how through semi-structured interviews, co-creation workshops and generation of user profiles (also known as personas), the participation of indigenous producers and translators was actively incorporated, and traditional knowledge (such as the tracking of the phases of the moon) was integrated into the design of the newsletters. Creating a participatory atmosphere to provoce group discussions.